Perspectives pour la paix mondiale à une époque de turbulence : Les États-Unis et les crises internationales - James, Patrick; Hristoulas, Athanasios (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
Recent events in world politics raise Fundamental doubts about the reasons behind conflict, crisis and war. What, for example, causes a state to become involved in an international crisis ? In an attempt to answer that question, the present study focuses on the experiences of a leading member of the international System over a sustained period of time, specifically, the United States in the post-World War 11 era. Ultimately, in order to develop a more comprehensive explanation of activity by the United States in international crises, this investigation combines external factors with others from within the state. Following a brief review of the research program on conflict linkage, internal attributes with potential relevance to involvement by states in crises are identified. External influences on foreign policy, consistent with the tradition of realpolitik, also are specified. These elements then are combined in a model of conflict linkage. Using data pertaining both the US as a polity and an actor in the international System, propositions derived from the model are tested in the crisis domain. The study concludes with some recommendations for further research on the linkage of domestic and foreign conflict, with particular reference to the explanation of crises.